Key Factors for Thymic Function and Development - Shichkin, Valentin P.; Antica, Mariastefania (Frontiers in Immunology, 2022)
The thymus is the organ responsible for T cell development and the formation of the adaptive immunity function. Its multicellular environment consists mainly of the different stromal cells and maturing T lymphocytes. Thymus-specific progenitors of epithelial, mesenchymal, and lymphoid cells with stem cell properties represent only minor populations. The thymic stromal structure predominantly determines the function of the thymus. The stromal components, mostly epithelial and mesenchymal cells, form this specialized area. They support the consistent developmental program of functionally distinct conventional T cell subpopulations. These include the MHC restricted single positive CD4+ CD8- and CD4- CD8+ cells, regulatory T lymphocytes (Foxp3+), innate natural killer T cells (iNKT), and γδT cells. Several physiological causes comprising stress and aging and medical treatments such as thymectomy and chemo/radiotherapy can harm the thymus function. The present review summarizes our knowledge of the development and function of the thymus with a focus on thymic epithelial cells as well as other stromal components and the signaling and transcriptional pathways underlying the thymic cell interaction. These critical thymus components are significant for T cell differentiation and restoring the thymic function after damage to reach the therapeutic benefits.